Hypoglycemic effect of Carica papaya leaves in streptozotocin-induced diabetic rats - Juárez-Rojop Isela Esther; Díaz-Zagoya Juan C; Ble-Castillo Jorge L; Miranda-Osorio Pedro H; Castell-Rodríguez Andrés E; Tovilla-Zárate Carlos A; Rodríguez-Hernández Arturo; Aguilar-Mariscal Hidemi; Ramón-Frías Teresa; Bermúdez-Ocaña Deysi Y (BMC, 2012)
Abstract Background Traditional plant treatment for diabetes has shown a surging interest in the last few decades. Therefore, the purpose of this study was to assess the hypoglycemic effect of the aqueous extract of C. papaya leaves in diabetic rats. Several studies have reported that some parts of the C. papaya plant exert hypoglycemic effects in both animals and humans. Methods Diabetes was induced in rats by intraperitoneal administration of 60 mg/kg of streptozotocin (STZ). The aqueous extract of C. papaya was administered in three different doses (0.75, 1.5 and 3 g/100 mL) as drinking water to both diabetic and non-diabetic animals during 4 weeks. Results The aqueous extract of Carica papaya (0.75 g and 1.5 g/100 mL) significantly decreased blood glucose levels (p<0.05) in diabetic rats. It also decreased cholesterol, triacylglycerol and amino-transferases blood levels. Low plasma insulin levels did not change after treatment in diabetic rats, but they significantly increased in non-diabetic animals. Pancreatic islet cells were normal in non-diabetic treated animals, whereas in diabetic treated rats, C. papaya could help islet regeneration manifested as preservation of cell size. In the liver of diabetic treated rats, C. papaya prevented hepatocyte disruption, as well as accumulation of glycogen and lipids. Finally, an antioxidant effect of C. papaya extract was also detected in diabetic rats. Conclusions This study showed that the aqueous extract of C. papaya exerted a hypoglycemic and antioxidant effect; it also improved the lipid profile in diabetic rats. In addition, the leaf extract positively affected integrity and function of both liver and pancreas.